(untitled) (Journal of Engineering Studies and Research, 2023)
The calculations were done for a wastewater treatment plant that had mechanical, biological, and sludge processing stages and served a population of about 11,100 people. Domestic wastewater, storm water, and industrial water collected from businesses that release into the sewage system are all treated at the treatment plant. The STAS 6953-81 method was used in this research to determine the total suspended solids content. The purification plant’s efficiency in removing these substances was assessed using measurements taken from both the influent and effluent. The quantities of coarse material (by weighing) retained from the sewage treatment plant using the two types of screens were also determined. It was observed that the efficiency of the treatment plant was over 98%.